Legal History in Lampung Province: A Study Using Historical Methods - Abdurrachman, Abdurrachman; Setiawan, Johan; Zakaria, Nurhijrah Binti (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aims to examine the development of legal history in Lampung Province using historical methods as the primary approach. The study explores the dynamics of the legal system from the pre-colonial period, based on customary law, through the colonial period with the dominance of Western law, to the post-independence period, marked by the integration of national law with local values. Historical methods are used through heuristics, source criticism, interpretation, and historiography to produce an objective and systematic historical reconstruction. The results indicate that law in Lampung has undergone a process of acculturation between customary law, based on the values of piil pesenggiri, and the formal state legal system. Customary law functions not only as a traditional norm but also as a living law that regulates social interactions and resolves conflicts within society. This research confirms that the continuity of customary law within the national legal system reflects the importance of local wisdom in the development of inclusive and contextual law.